(untitled) (Journal on studies and research of academic knowledge, 2021)
The work focuses on the components that intervened in the management for the creation of the National University of Itapúa, during the years 1995-1996. The general objective was to analyze the social, cultural and political components that intervened in the management for its creation. The research was of a qualitative nature, topical type narrative design. The sample size, called "Theoretical" was 37 Key Informants and the data collection instrument was the interview. To evaluate the data, the Atlas.ti program was used and the triangulation of the codes, of greater density used, was carried out from the interview with the Principal of the UNI. The most relevant results showed that the main manager of the creation of the National University of Itapúa was the lawyer Lorenzo Luciano Zacarías. The main political component was the ideologue’s relationship with national, departmental and municipal authorities. The social purpose was to avoid uprooting and the Cultural one was the preference shown by the citizens with respect to the careers of Medicine and Engineering. It is concluded that, thanks to the tenacity, the futuristic vision, the political capacity and the social commitment of the managing group, the city of Encarnación obtained the socio-cultural and economic benefit of having a Public-Autonomous University and avoiding the emigration of the university population.